Torsion of the Gravid Uterus - Jahan, Samsad; Jalil, Masuma; Khan, Masuda Islam; Jesmin, Suha; Rumman, Umme (Ibrahim Medical College Journal, 2010)
Ibrahim Med. Coll. J. 2009; 3(2): 78-79 DOI: 10.3329/imcj.v3i2.4223